ENHANCING CUSTOMER SATISFACTION THROUGH IOT-BASED SMART PARKING SYSTEMS IN SHOPPING MALLS - Juhari, Nur Hafizah; Yuki, Goh; Khan, Puteri Ameera Mentaza; Khair, Nurhayati (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
An intelligent parking system with IoT technology is vital in shopping mall parking because it enhances convenience and efficiency for shoppers and visitors. The system can assist in reducing several problems that impact the users, such as wasting time finding parking and paying parking fees at the auto-pay machines. Thus, this study examines the components of smart parking systems that affect customer satisfaction levels. The smart payment system, sensor system, navigation system, security system, parking reservation system, and electric vehicle charging system are among the components. Data was gathered via questionnaires from 100 respondents who were at least 16 years old and had experience driving vehicles to shopping malls in Kuala Lumpur. The results from the Relative Important Index indicate that the smart payment system is the most influential component of IoT-based smart parking systems in affecting customer satisfaction at shopping malls. Therefore, the shopping operator, developer, property manager, and future researcher can emphasise the most important elements of the intelligent parking system to enhance management and increase customer satisfaction. In addition, the smart parking system should be implemented in Malaysia to ensure that the parking system has advanced and comprehensive facilities for visitors.